PMMA-co-EHA cements for osteoprotheses - Ferreira, Bárbara Joana Martins Leite (2012)
The main purpose of this thesis was to produce new formulations of PMMA-co- EHA and study its feasibility as being an alternative to traditional PMMA bone cements. Thus, were originally produced several co-polymers of PMMA-co-EHA and its mechanical properties and in vitro behaviour were evaluated. The copolymers were obtained by radical polymerization and several formulations were produced by partial replacement of MMA (up to about 50%) for EHA. Overall, the results suggest that the partial replacement of MMA by EHA decreased the modulus of the materials and, consequently, increased its flexibility. Then, PMMA commercial beads were added to PMMA-co-EHA formulations (to get bone cement) and the general properties of the resulting bone cements were evaluated. In general, the results revealed that the partial replacement of MMA by EHA led to beneficial changes in curing parameters (there was a reduction of the peak temperature and an increase of curing/setting time), in the in vitro behaviour (the water capacity increased) and in the mechanical properties (the bending strength increased) of new cements. The in vitro cellular response of new formulations of PMMA-co-EHA was compared with that of traditional PMMA bone cement. To this end, we tested the cell adhesion and proliferation of osteoblast-like MG63 cells and human cells from bone marrow. The results revealed that both types of cells were able to attach and proliferate in both formulations. The only exception was observed for the formulation prepared with the highest percentage of EHA, where a few cells that adhere failed to proliferate. Moreover, it was found that increasing the amount of EHA in cement led to an increasing inhibition of cell growth, especially during the first week of culture. This was related to increased water uptake capacity by the new formulations and consequent release of some of its toxic components. Finally, PMMA commercial beads were partially replaced by HA particles and the influence of this substitution on the curing parameters, the mechanical properties and in vitro behaviour of the resulting composites was also evaluated. Incorporation of HA into the bone cements induced a number of significant changes in its final properties: 1) decrease the peak temperature; 2) increase of curing time, 3) increasing the value of elastic modulus accompanied by decrease of the strength/tension. This last finding was related to poor interfacial adhesion between the various components of the bone cements and a heterogeneous distribution (possible agglomeration) of HA particles.